Pertumbuhan dan Produksi Tumpangsari Rumput Gajah Odot dengan Kedelai pada Berbagai Jarak dan Waktu Tanam - Tumanggor, Jon Andri Efendi; Sutarno, S; Widjajanto, Didik Wisnu (Journal Galung Tropika, 2022)
Diversification is one solution to increase crop yields. The intercropping system is an example of agricultural diversification. The aim of this study is to determine the effect of various elephant grass cv. odot planting distances and various soybean planting times on the growth and production of elephant grass cv. odot and soybean in an intercropping system. The research was conducted from September 2020 - February 2021 in Kalongan Village, East Ungaran Sub-district, Semarang District, Central Java Province. The 2 × 4 factorial experiment with randomized block design and 3 repeats were used in this study. The first factor is planting distances of elephant grass cv. odot (J) which are 60 × 90 cm (J1) and 45 × 90 cm (J2). The second factor is soybean planting times (T), which were 26, 19, 12, and 5 days before trimming of elephant grass cv. odot for T1, T2, T3 and T4. The parameters observed for elephant grass cv. odot were height, the number of tillers and production, while for soybean were height, the number of leaves and productivity. The data obtained were processed using Analysis of variance (ANOVA) and then the parameters that had a significant effect were tested with Duncan's Multiple Range Test (DMRT) at a 5% level. Treatment of planting distances and planting times did not significantly affect the growth of elephant grass cv. odot, soybean growth, and productivity of elephant grass cv. odot. Planting distances treatment did significantly affect soybean productivity. The combination treatment of 60 × 90 cm planting distance on elephant grass cv. Odot and 26 days before trimming of elephant grass cv. odot on soybean planting time is the best result for intercropping of elephant grass cv. odot and soybean.